Ecolodge Exploration: a projective design for the Flamingo district in the Everglades National Park - Steward, Kelsey J. (Kansas State University, 2017)
Nature based tourism is a growing trend across the world today. Ecotourism is a specific nature based tourism type, defined by the International Ecotourism Society (TIES) as “Responsible travel to natural areas that conserves the environment and improves the well-being of local people.” The ‘ecolodge,’ is a term that refers to the site and structure where ecotourists stay and where ecotourism activities occur. The intention of an ecolodge is to find a balance between three factors: conservation, local communities, and interpretation for travelers and workers. Every ecolodge is unique in form and function to uphold sustainability best practices and to meet specific environmental and climatic needs of a region. As more and more tourists choose to travel to environmentally sensitive areas of the world, ecolodge use must increase in order to preserve environmental and cultural assets (Honey, 2008). In other countries, like Costa Rica and Kenya, many ecolodges have successfully balanced these three components creating an overall trend towards ecolodges and ecotourism operations, shifting away from traditional accommodation types. However, as the U.S. tourism market continues to grow, there is yet to be a notable ecolodge presence. Some ecotourism experts would argue that true ecotourism--equally finding balance between conservation, guest interpretation, and community support--will never be possible to create in the U.S. Many believe it is the ‘supporting local communities’ aspect of ecotourism which cannot be met. The treatment of indigenous people, as well as the structure of the nation’s economy in the U.S. is different compared to developing countries where ecolodge design has found success. Interestingly, certified sustainable site development is becoming prevalent in the U.S. Frameworks such as LEED and SITES are used to improve the rigor of sustainability design. Design guidelines for ecolodges share similar goals with LEED and SITES. But ecolodge design is not prevalent in the U.S. This may be due to the lack of an international ecolodge certification system. If the ecotourism industry can progress from ecolodge guidelines (which are largely unknown) to an international ecolodge certification, truly authentic ecolodges will become the standard (Mehta, 2007). To explore how ecolodges can be used in a U.S. National Park, this project focuses on the Flamingo District in the Everglades National Park, Florida. A projective design methodology is used. The data collection methods include precedent studies, interviews, on-site observation, and site analysis. Flamingo, located in the southernmost point of the Everglades was destroyed by hurricane Katrina in 2005. The National Park Service is seeking a business concessioner to 1) oversee the construction of new lodging area, and 2) operate all business activities—recreation rentals, marina operations, general store, and dining—in the district. The goal of this research project is to create an ecolodge design that can serve Flamingo’s needs and serve as a model for future ecolodge design in U.S. National Parks.
Keywords: Ecotourism; Landscape architecture; Sustainability; National parks; EvergladesEcolodge